Retrograde Ventriculoperitoneal Shunt Migration - Muhammad Junaid; Syed Sarmad Bukhari; Anisa Kulsoom; Muhammad Khalid (Gomal Journal of Medical Sciences, 2014)
Ventriculoperitoneal shunts are one of the common treatments for management of hydrocephalus and shunt migration is a significant problem with a reported incidence of up to 10%. A 4 month old infant presented to us with a previous history shunt placement twice and an endoscopic third ventriculostomy and repeated meningtitis which prompted removal of the shunts. She presented with active meningitis again and was treated appropriately and a Chabbra shunt was placed which migrated intraventricularly after 2 and a half month. Infection was believed to be a prompting factor here. A Pudenz shunt was subsequently placed and she had a good recovery at 6 months of followup.